2022
DOI: 10.1016/j.pmedr.2021.101675
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and costs of an implemented primary HPV cervical screening programme in Sweden – A population based cohort study

Abstract: Highlights In an HPV-based cervical screening programme more HSIL + cases was detected but the clinical effectiveness comes with higher rates of colposcopy and clinical irrelevant findings. In an HPV-based cervical screening programme two thirds of the cost, come from screening visits with sampling. From a health economic perspective, our data emphasize the need for considering alterations in the screening programme including more specific triage analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…Another study predicting the cost-effectiveness of screening with hrHPV testing showed a decrease in the incremental cost-effectiveness ratio (ICER) of (USD −6.16) relative to conventional cervical cytology. Quality-adjusted life-years (QALYs) were 386.98 for cytology and 390.80 for hrHPV-based testing, respectively [ 58 , 59 ]. A combination of LBC and HPV testing methods is called co-testing.…”
Section: Review Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study predicting the cost-effectiveness of screening with hrHPV testing showed a decrease in the incremental cost-effectiveness ratio (ICER) of (USD −6.16) relative to conventional cervical cytology. Quality-adjusted life-years (QALYs) were 386.98 for cytology and 390.80 for hrHPV-based testing, respectively [ 58 , 59 ]. A combination of LBC and HPV testing methods is called co-testing.…”
Section: Review Resultsmentioning
confidence: 99%
“…The most common type is HPV 16 (50% of cases). Other oncogenic HPV types responsible for persistent cervical tissue infections include HPV 18,31,33,35,39,45,51,52,56,58,59, 66, and 68. However, infection alone is not sufficient for disease development.…”
Section: Introductionmentioning
confidence: 99%
“…Para que la infección por el VPH, cause lesiones intraepiteliales (LIE) o Ca de cuello uterino, debe existir una cronicidad de la infección, es por ello que, se presenta el contagio por VPH mucho antes de que se presenten las LIE (9). En personas con inmunosupresión, como en el VIH, se ve un aumento de la frecuencia de las LIE del 4,6% en mujeres, del 7,2% en varones y del 18,5% en HSH (10).…”
Section: Palavrasunclassified
“…Today, the most commonly used method of triage is cytology. Increases in colposcopies and in detection of benign or low-grade dysplasia with HPV screening compared to cytology screening are reported from the Netherlands among other countries, even though triage is implemented [ 1 , 12 , 13 ]. This lower specificity of the HPV test dictates the necessity of use of other triage tests in current HPV screening strategies, which can select women for colposcopy more accurately [ 5 ] and thus minimize the clinically irrelevant findings.…”
Section: Introductionmentioning
confidence: 99%